Tinjauan Kriminologi Terhadap Tindak Pidana Niaga Bahan Bakar Minyak Ilegal Di Kota Gorontalo (Studi Kasus Polda Gorontalo) - Pratiwi, Faradilah Regitha; Badu, Lisnawaty W.; Mandjo, Julius T. (CV. ITTC INDONESIA, 2023)
One form of misuse of oil and gas is the abuse of fuel subsidies which has been rife in recent years. This study aims to identify and analyze the factors that influence a person who misuses fuel oil in Gorontalo from a criminological perspective, and also to determine law enforcement efforts in the abuse of fuel trade in Gorontalo. The research method uses empirical legal research. The factors behind the occurrence of the crime of trading fuel without a permit in Gorontalo City are the economic pressures that squeeze, the lack of public understanding of the crime of trading fuel, and the easy factor to get fuel for re-sale, and weak supervision by related parties. The legal efforts taken in dealing with cases of abuse of fuel trade in Gorontalo are by carrying out supervision by coordinating with related parties, and carrying out investigations and investigations.